Analysis of T and B Cell Epitopes to Predict the Risk of de novo Donor-Specific Antibody (DSA) Production After Kidney Transplantation: A Two-Center Retrospective Cohort Study - Sakamoto, Shintaro; Iwasaki, Kenta; Tomosugi, Toshihide; Niemann, Matthias; Spierings, Eric; Miwa, Yuko; Horimi, Kosei; Takeda, Asami; Goto, Norihiko; Narumi, Shunji; Watarai, Yoshihiko; Kobayashi, Takaaki (Frontiers in Immunology, 2020)
Risk prediction of de novo donor specific antibody (DSA) would be very important for long term graft outcome after organ transplantation. The purpose of this study was to elucidate the association of eplet mismatches and predicted indirectly recognizable HLA epitopes (PIRCHE) scores with de novo DSA production. Our retrospective cohort study enrolled 691 living donor kidney transplantations. HLA-A, B, DRB and DQB eplet mismatches and PIRCHE scores (4 digit of HLA-A, B, DR and DQ) were determined by HLA matchmaker (ver 2.1) and PIRCHE-II Matching Service, respectively. Weak correlation between eplet mismatches and PIRCHE scores was identified, although both measurements were associated with classical HLA mismatches. Class II (DRB+DQB) eplet mismatches were significantly correlated with the incidence of de novo class II (DR/DQ) DSA production [8/235 (3.4%) in eplet mismatch≤13 vs. 92/456 (20.2%) in eplet mismatch≥14, p<0.001]. PIRCHE scores were also significantly correlated with de novo class II DSA production [26/318 (8.2%) in PIRCHE≤175 vs. 74/373 (19.8%) in PIRCHE≥176, p<0.001]. Patients with low levels of both class II eplet mismatches and PIRCHE scores developed de novo class II DSA only in 4/179 (2.2%). Analysis of T cell and B cell epitopes can provide a beneficial information on the design of individualized immunosuppression regimens for prevention of de novo DSA production after kidney transplantation.